PENGARUH LATIHAN PARALLEL BAR DIPS TERHADAP KEKUATAN OTOT LENGAN DAN BAHU PERGURUAN PENCAK SILAT TANGAN MAS PEKANBARU - Dewantara, Wisnu Rahmat; Ramadi, Ramadi; Vai, Aref (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research is done to find out if there is any influence of Parallel bar dips exercise on the muscle strength of the arm and shoulder of male athletes pencak Silat tangan mas Pekanbaru, So that at the time of the championships male athletes tangan Mas still has a deficiency in the technique of takedowns. The takedowns done by male athletes of tangan mas can still be easily withheld and foiled by opponents. This is due to the strength of the muscles of the arm and shoulders in the male school Pencak Silat tangan Mas Pekanbaru is still lacking. This form of research is research with experimental treatment (experimental), With a population of male Pencak Silat tangan mas Pekanbaru, The data in this research is the whole active male athlete Pencak Silat tangan mas that amounted to 6 people. The instrumen performed in this research is by using expanding Dynamometer which aims to measure the strength of the muscles of the arms and shoulders. Afterwards, the data is processed with statistics, to test the normality with lilliefors test at a significant level ∝ 0.05. Hypothesis proposed is the influence of parallel bar training dips on the strength of the muscle arm and shoulder male pencak Silat tangan mas Pekanbaru. Based on test analysis t produces Tcount of 7.91 and Ttable 2.015 which means Tcount > Ttable. Based on the analysis of statistical data, there is an average Pre-Test 21.16 and the average post-test of 30.83, then the data is normal. Thus, it can be concluded that there is the influence of the parallel bar dips to the muscle strength of the arm and shoulder of male pencak Silat Mas Pekanbaru.Key Words: Parallel Bar Dips, Arm and shoulder muscle strength